If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 1.72 Reorder the terms: -3 + 4x = 1.72 Solving -3 + 4x = 1.72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = 1.72 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 1.72 + 3 4x = 1.72 + 3 Combine like terms: 1.72 + 3 = 4.72 4x = 4.72 Divide each side by '4'. x = 1.18 Simplifying x = 1.18
| r^3-11r^2+36r-36= | | 7m-6=65 | | 9-3r=2h | | -5(x-4)-3(-2-x)=x-2 | | 42+17r=-14r+-42 | | 4.2+2=10 | | 180=7x-13+2x+2+4x+9 | | 8=5-3x-6 | | X-5=2x-24 | | -25=5(w-7)-7w | | 4u^4+68u^2+280=0 | | 8=4-6b+2b | | 15=6-3n | | 72yp-12y= | | 5x+500=150 | | -9=3+5a-7 | | -4.9x^2+7.4x+10.9=0 | | 190=7x-13+2x+2+4x+9 | | 5y+13+5-3y=m | | 4(2y-4)=2(y-13) | | 60-(3c+4)=4c+24+c | | 14-6x= | | -4.9x^2+7.4t+10.9=0 | | Lne^2=6 | | 4+5(3x-x)=4(8+2x) | | 2(-2n+5)=4-6n | | 7.36=-0.8(2x-1.2) | | 2(3+3x)=78 | | -9+6x=-3[3-2x] | | -13=m+3-8 | | 10x+20x=12x | | 4p+3=-13 |